Effectiveness of timed and targeted counselling about feeding and caring practices for infants and young children to mothers in West Bank: a randomised controlled trial. (August 2017) - Al–Rabadi, Hana S; Sharif, Nuha E
Abstract: Background: Restricted access to health facilities in some Palestinian localities is believed to contribute to little knowledge and poor infant and young child feeding (IYCF) and care practices among mothers. The objective of this study was to assess the effectiveness of a community approach called Timed Targeted Counselling in improving mothers' knowledge and practices of IYCF in four remote villages surrounding Bethlehem in the West Bank. Methods: We did a randomised controlled trial in four villages. All mothers of infants born between March 1, 2011, and April 30, 2011, were identified by community health workers (CHWs) and randomly assigned to the intervention or comparison group. Randomisation was done at the individual level, four villages who had similar characteristics were identified and all newborns during the months of March and April, 2011, were assigned randomly into intervention and comparison groups, univariate, and multivariate analysis were applied. CHWs targeted the intervention group with key messages and support for positive IYCF and caring practices during two organised home visits (sometimes three depending on their counselling) throughout 12 months. Women in the comparison group were not exposed to any messages; they were visited only for data collection. Baseline and postintervention data from a questionnaire, designed for the purpose of the study, were collected for both groups at the end of 12 months. Ethical approval was given and informed consent obtained from participants. The primary endpoint was behavioural caring practices of mothers towards their children. We did univariate and multivariate statistical analysis were planned to be done using SPSS version 17. Findings: We enrolled 118 mothers in the study and randomly assigned them to the intervention group (n=66) or the comparison group (n=52). IYCF and caring practices improved significantly among mothers in the intervention group: exclusive breastfeeding up to 6 months increased from 27% (18 of 66 women) to 70% (46 women; OR 29, 95% CI 8·02–108); breastfeeding of children aged 1 year increased from 56% (37) to 83% (55; 2·94, 1·03–8·41); timely introduction of complementary meals increased from 38·5% (25) to 67% (44; 83·6, 17·24–40·5); rubbing of salt on infant skin and umbilical cord decreased from 54·5% (36) to 3% (3; 0·033, 0·006–0·19); recognition of danger signs increased from 15% (10) to 48% (32; 3·96, 0·17–9·2); and, bathing of newborns within 24 h after birth decreased from 68·2% (45) to 32% (21; p<0·0001 for all comparisons). No behavioural changes were recorded among mothers in the comparison group. During the study period, fewer disease episodes were reported in the intervention group than in the comparison group for diarrhoea (10 cases vs 25 cases), respiratory illness (15 vs 33), common cold (39 vs 50), fever (20 vs 31), and ear infections (7 vs 32 cases). Interpretation: Timed Targeted Counselling proved very effective for improvement of a range of IYCF and caring practices. Because of contextual similarities in most Palestinian localities, scale-up for TTC is recommended for other areas in West Bank (Gaza, occupied Palestine territory). Funding: World Vision Jerusalem.